Effect of the new contract on GPs' working lives and perceptions of quality of care: a longitudinal survey - Whalley, Diane (Royal College of General Practitioners, 2008)
BACKGROUND: An ambitious pay-for-performance system was implemented in UK general practice in 2004 amid doubts that it could improve both the working lives of doctors and quality of care. AIM: To evaluate doctors' perceptions of their working lives and quality of care before and after the new contract. DESIGN OF STUDY: Longitudinal questionnaire survey. SETTING: England, UK. METHOD: A longitudinal postal survey of English GPs in February 2004 and September 2005. Measures included reported job satisfaction (7-point scale), hours worked, income, and impact of the contract. RESULTS: Responses were available from 2105 doctors in 2004 and 1349 in 2005. Mean overall job satisfaction increased from 4.58 out of 7 in 2004 to 5.17 in 2005. The greatest improvements in satisfaction were with remuneration and hours of work. Mean reported hours worked fell from 44.5 to 40.8. Mean income increased from an estimated £73 400 in 2004 to £92 600 in 2005. Most GPs reported that the new contract had increased their income (88%), but decreased their professional autonomy (71 %), and increased their administrative (94%) and clinical (86%) workloads. After the introduction of the contract doctors were more positive than they had anticipated about its impact on quality of care. CONCLUSION: GPs' job satisfaction increased after the introduction of the new contract, despite perceptions of negative consequences for workload and autonomy. GPs reported working fewer hours with a higher income, and their expectations regarding the impact of the contract on quality of care had been exceeded.